A Study of Good Governance Index in Yogyakarta Special Region Between 2012 and 2016 - Achmad Ubaidillah (Magister Administrasi Publik, 2017)
This study assesses the progress of good governance index in Yogyakarta between 2012 and 2016. Kemitraan (Partnership for Governance Reform) developed the Yogyakarta governance index of 2012 based on the IGI (Indonesia Governance Index)’s methodology. The author used the same methodology to develop Yogyakarta governance index of 2016 based on newly collected data on government, bureaucracy, civil society and economic society in Yogyakarta. This paper compares Yogyakarta good governance index for 2012 and 2016. The index comprises scores on three levels, interalia: the arena, principles and actual policy. The paper introduces and describes the three tier structure and index processing. Results of the comparison of the index for 2012 and 2016 shows that in general Yogyakarta governance index increased from the level of fairy good (6.80) in 2012 to good (7.93) in 2016. Subsequently, the scores that comprise the arena and principle levels were analyzed to determine the contribution of each to the total governance index, and afterwards determine the contribution of each principle to the score of each arena. The results of the analysis procedure indicates the possibility that the increase in governance index may be linked to new special status Law No.13 of 2012 for Yogyakarta. Prior to 2012, the special status of Yogyakarta special administration was shrouded in uncertainty. However, with the passage of Law No.13/2013, the special status of the province is now codified, and today forms the legal basis for policy making in this province. This paper limits itself to indicators that point to the association between the governance and the enactment of the law, and does neither go as far as analyzing the impact that the enactment of the special status law has had on policies, nor evaluate the impact that policy changes made in the aftermath of the implementation of the special status law on the performance of the index.